Marginal adaptation, solubility and biocompatibility of TheraCal LC compared with MTA-angelus and biodentine as a furcation perforation repair material - M. A. Alazrag; A. M. Abu-Seida; K. M. El-Batouty; S. H. El Ashry (BMC, 2020)
Abstract Background This study evaluated the marginal adaptation, solubility and biocompatibility of TheraCal LC compared with mineral trioxide aggregate (MTA-Angelus) and Biodentine when used as a furcation perforation repair material. Methods The marginal adaptation was assessed by scanning electronic microscope and presence of any gap between the dentin surface and filling material in each quadrant of the sample was analyzed at 1000 X magnification. The solubility was measured after one week by the ISO standard method. Biocompatibility was evaluated by the inflammatory response and radiography after one month and three months of repair of experimental furcation perforations in dog's teeth. Results There were significant differences in the marginal adaptation, solubility and biocompatibility of the tested materials (P < 0.05). TheraCal LC showed the highest frequency distribution of gap presence that was followed by the MTA-Angelus then Biodentine. The least soluble material after one week was TheraCal LC that was followed by the MTA-Angelus and Biodentine. After one month and three months, TheraCal LC showed the highest inflammatory response and highest frequency distribution of radiolucency that was followed by the Biodentine then MTA-Angelus. Conclusion Unlike Biodentine, TheraCal LC is incapable of alternating the MTA in furcation perforation repair due to its poor biocompatibility and poor marginal adaptation.